2021
DOI: 10.3389/fpubh.2020.587374
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic SARS-CoV-2 Carriers: A Systematic Review and Meta-Analysis

Abstract: Asymptomatic cases of SARS-CoV-2 can be unknown carriers magnifying the transmission of COVID-19. This study appraised the frequency of asymptomatic individuals and estimated occurrence by age group and gender by reviewing the existing published data on asymptomatic people with COVID-19. Three electronic databases, PubMed, Embase, and Web of Science (WoS), were used to search the literature following the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The study popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(121 citation statements)
references
References 78 publications
9
105
5
2
Order By: Relevance
“…High seropositivity in children might be due to continued operation of public schools throughout the epidemic. As children are more likely to experience mild symptoms than adults, 11 this finding suggests that school-aged children may contribute to active transmission, and controlling infections in this sub-population is essential to reduce the spread of SARS-CoV-2. We also found that most individuals reported practicing strict physical distancing or masking behavior outside of the home, though this did not have a significant impact on the seroprevalence.…”
Section: Discussionmentioning
confidence: 99%
“…High seropositivity in children might be due to continued operation of public schools throughout the epidemic. As children are more likely to experience mild symptoms than adults, 11 this finding suggests that school-aged children may contribute to active transmission, and controlling infections in this sub-population is essential to reduce the spread of SARS-CoV-2. We also found that most individuals reported practicing strict physical distancing or masking behavior outside of the home, though this did not have a significant impact on the seroprevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a significant correlation has been observed between pre-vaccination anti-SARS-CoV-2 antibodies titer and Pfizer BNT162b2 vaccine immunogenicity, whereby the anti-SARS-CoV-2 RBD (receptor binding domain) total antibodies response seems to be reduced (up to nearly eightfold) in patients with a baseline antibody level in the upper quartile [11]. Therefore, with 50% (or even more) of all SARS-CoV-2 infections remaining completely asymptomatic up to negativization of molecular testing [14,15], the organization of pre-vaccination serological surveys represents a reliable mean for unmasking all SARS-CoV-2 seropositive subjects in whom vaccine administration may be personalized, adapted, or even delayed based on their actual anti-SARS-CoV-2 antibodies status [16]. This would also enable the optimization of vaccine administration to those who may benefit most (i.e., baseline anti-SARS-CoV-2 seronegative subjects), thus contributing to at least partially overcoming the current vaccines' manufacturing bottleneck, which is causing a worldwide shortage of doses, and thus perpetuating new outbreaks and the potential for emergence of new mutant strains.…”
Section: Why?mentioning
confidence: 99%
“…During the pandemic children have been less affected than adults and SARS-CoV-2 was in most cases asymptomatic or with mild symptoms [3][4][5]. However, the development of a severe multisystem inflammatory syndrome in children (MIS-C) related to SARS-CoV-2 infection has been reported [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%